Studi Komparasi Pertumbuhan Ekonomi Indonesia Sebelum dan Ketika Terjadinya Pandemi Covid-19 - Khavid Normasyhuri; Ahmad Habibi; Erike Anggraeni (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2021)
COVID-19 is having an impact on health and the economy. COVID-19 puts pressure on world economic growth, including Indonesia's economic growth. Indonesia Government Regulations administered since March 2020 regarding to the prohibition of crowding at public places and social distancing have further limited the economical activities and even have an impact to the deceleration of economic growthThis research is a comparative quantitative research. The data used is secondary data before the occurrence of COVID-19, namely three months II 2018 three months III 2019 and when COVID-19 occurs, namely three months IV 2019 three months I 2021. The statistical tool used is SPSS Version 21. The test used is Paired Sample T-Test. As a result, there is a significant difference in economic growth before and after COVID-19 occurs. It is happened caused by an epidemic that spreads across the country affected the growth of the global economy decreasing no exception for Indonesia economic growth the effectiveness of social distancing policy that caused blockage economy activity and presentation of Indonesia's high exposure to COVID-19 and character of society when facing economy on the epidemic situation as the factor of Indonesias economic growth experiencing a recession in the negative direction.